Wilson’s Disease - Trindade, Miguel (2024)
WD is rare, and the diagnostic suspicion should be high in young patients with subacute or acute chronic liver disease: a diagnosis made in time can avoid a liver transplant. The diagnostic workup was not straightforward, and genetic testing was necessary to confirm the diagnosis To our knowledge, this is the first report of this compound heterozygote genotype. The c.3402del mutation has been described as liver-predominant in heterozygous and neurologically predominant in homozygous patients. The c.3061-12T>A mutation is described as neurologically predominant. The evolution of our patient remains to be seen in the long-term follow-up.